Igf2 pathway dependency of the Trp53 developmental and tumour phenotypes - Haley, Victoria L (WILEY-VCH Verlag, 2012)
Insulin-like growth factor 2 (IGF2) and the transformation related protein 53 (Trp53) are potent regulators of cell growth and metabolism in development and cancer. In vitro evidence suggests several mechanistic pathway interactions. Here, we tested whether loss of function of p53 leads to IGF2 ligand pathway dependency in vivo. Developmental lethality occurred in p53 homozygote null mice that lacked the paternal expressed allele of imprinted Igf2. Further lethality due to post-natal lung haemorrhage occurred in female progeny with Igf2 paternal null allele only if derived from double heterozygote null fathers, and was associated with a specific gene expression signature. Conditional deletion of Igf2(fl/fl) attenuated the rapid tumour onset promoted by homozygous deletion of p53(fl/fl). Accelerated carcinoma and sarcoma tumour formation in p53(+/−) females with bi-allelic Igf2 expression was associated with reductions in p53 loss of heterozygosity and apoptosis. Igf2 genetic dependency of the p53 null phenotype during development and tumour formation suggests that targeting the IGF2 pathway may be useful in the prevention and treatment of human tumours with a disrupted Trp53 pathway.